2015
DOI: 10.1039/c4cp04360j
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cisplatin and two potential antitumoral platinum(ii) complexes with a model lipid membrane: a combined NMR and MD study

Abstract: In this study, the interaction of cisplatin (1) and two potential antitumoral Pt(II) complexes (2 and 3) with a model DMPC bilayer was investigated by multinuclear NMR spectroscopy and MD simulations in order to understand its implication for the different antitumoral properties shown by the three complexes. In particular, (31)P, (13)C and (2)H solid state NMR experiments were performed to obtain information on the phase structure, phase transitions and structural and dynamic changes in the phospholipid bilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…The only computational work which is directly comparable with the present study is the paper of Nierwzicki et al (99) where the permeability of cisplatin in a pure DMPC bilayer was reported as 6.67 10 −7 • −1 . This value is of the same order of magnitude as our result for pure DOPC bilayer.…”
Section: Permeability In Comparison To Experimental Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The only computational work which is directly comparable with the present study is the paper of Nierwzicki et al (99) where the permeability of cisplatin in a pure DMPC bilayer was reported as 6.67 10 −7 • −1 . This value is of the same order of magnitude as our result for pure DOPC bilayer.…”
Section: Permeability In Comparison To Experimental Resultssupporting
confidence: 84%
“…There is a high energy barrier in the center of the membrane, which is expected for such hydrophilic compound as cisplatin. The height of the barrier is the smallest for pure DOPC membrane (~40 kJ/mol) which is comparable to previous results obtained in a pure 1,2-dimyristoyl-sn-glycero-3phosphocholine (DMPC) membrane (~50 kJ/mol) (99). For normal membrane with 0% cholesterol it is much higher (~62 kJ/mol) and increases even more with the increase of CHL content (up to 70 kJ/mol).…”
Section: Permeation Of Cisplatinsupporting
confidence: 86%
“…Notwithstanding, it causes severe side effects such as neurotoxicity and cellular resistance that are thought to be related to the interplay of cisplatin with biological membranes. Over the years, considerable studies regarding cisplatin interaction with model membranes have been performed [56,[78][79][80][81][82][83]. Particular attention has been paid to anionic phospholipids, such as PS -as they play crucial roles in several cell functions [84]-and their influence in cisplatin-lipid interaction.…”
Section: Studies Using Dsc and Langmuir Isotherms Demonstrated That Pmentioning
confidence: 99%
“…Results indicated that phospholipids such as phosphatidylcholine (PC) make the model cellular membrane more fluidly and would facilitate the passing through of cisplatin for effective intracellular accumulation . In most recent research of the design of Pt(II)‐based drugs, ligands with suitable properties such as polarity and hydrophilicity, which may regulate passive diffusion, are being the focus . Nuclear magnetic resonance (NMR) spectroscopy has been applied to study the interaction of cisplatin as well as potential antitumor complexes with a lipid bilayer, which showed that the structures of the complexes determined different effects on the bilayer structure and mobility and further the depth of their penetration into the bilayer .…”
Section: Introductionmentioning
confidence: 99%
“…10 Nuclear magnetic resonance (NMR) spectroscopy has been applied to study the interaction of cisplatin as well as potential antitumor complexes with a lipid bilayer, which showed that the structures of the complexes determined different effects on the bilayer structure and mobility and further the depth of their penetration into the bilayer. 10 Such kind of investigations contribute significantly to the understanding of complex-lipid interactions and provide fundamental insights into structural design of new drug candidates. However, due to the difficulty in data acquirement or complexity in interpretation of IR and NMR spectra from real biological membranes, only simple model systems of lipid bilayers were investigated, which might not uncover the real situation in complex cellular membrane systems.…”
Section: Introductionmentioning
confidence: 99%